Influence of Ambient Relative Humidity on Seasonal Trends of the Scattering Enhancement Factor for Aerosols in Chiba, Japan - Lagrosas, Nofel (Archīum Ateneo, 2019)
In this study, we used ground instruments, namely, a visibility meter, an integrating nephelometer, an aethalometer, a lidar, and a weather monitor, to measure the scattering enhancement factor, f(RH), which quantifies the effect of ambient relative humidity (RH) on aerosol light-scattering, and to generate a model of its annual variation in the city of Chiba, Japan. First, the f(RH) values were calculated with chemical analysis data. Second, visibility-meter and aethalometer data were used to model the monthly trends of f(RH) at 550 nm. The f(RH) values were higher during summer than during the other three seasons, which can be attributed to the general pattern of the regional climatology as well as the loading of different particle types into the lower troposphere. Third, the f(RH) values at 532 nm were obtained from lidar and aethalometer measurements. Low and constant f(RH) values were observed during November, whereas higher and increasing f(RH) values were observed during May. Also, dust events during March 2015 showed decreasing f(RH) with increasing RH .